HUBUNGAN KECEMASAN DAN DUKUNGAN KELUARGA DENGAN ACTIVITIES OF DAILY LIVING PADA LANSIA HIPERTENSI DI KELURAHAN CINERE TAHUN 2023 - Reihana Zakiya (2023)
The increase in the number of elderly at this time causes various health problems experienced due to the aging process. Generally, physical changes will have an impact on decreasing daily activities and psychological changes will cause anxiety which will affect the level of independence of the elderly. To meet the needs of carrying out daily activities, the elderly need the role of the family as a form of support. This study aims to analyze the relationship between anxiety and family support with activities of daily living for hypertensive elderly people in the Cinere Village in 2023. This type of research is quantitative with the method used is a cross-sectional observational approach with Spearman's rho data analysis. Sampling was carried out in May-June with a quota sampling technique of 164 respondents. Data were collected using the GAS, PSS-Fa and Barthel Index questionnaires. The three questionnaires have been tested for validity and reliability and have been proven to be valid and reliable. Based on the results of the data analysis that has been carried out, significant results are obtained P Value = 0.000 (<0.05), so that there is a relationship between the anxiety variable and activities of daily living and there is also a relationship between family support and activities of daily living with P Value = 0.000 . It can be concluded that anxiety involvement and family support are essential factors in fulfilling activities of daily living for elderly hypertensives to be able to control problems and prevent further complications.